2013
DOI: 10.1242/jeb.097220
|View full text |Cite
|
Sign up to set email alerts
|

Figure-ground discrimination behavior in Drosophila. I. Spatial organization of wing steering responses

Abstract: The behavioral algorithms and neural subsystems for visual figure–ground discrimination are not sufficiently described in any model system. The fly visual system shares structural and functional similarity with that of vertebrates and, like vertebrates, flies robustly track visual figures in the face of ground motion. This computation is crucial for animals that pursue salient objects under the high performance requirements imposed by flight behavior. Flies smoothly track small objects and use wide-field optic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(54 citation statements)
references
References 49 publications
4
47
3
Order By: Relevance
“…Specifically, flies rely on saccades to track the bar but rapidly engage the smooth optomotor reflex between saccades with a delay as small as 25 ms, consistent with other methods of measurement [7]. During inter-saccadic smooth movement, flies are still capable of perceiving and fixating a visual bar, the corollary of which is that bar tracking is little perturbed by movement of the visual panorama [29]. Robustly tracking the ground in closed-loop would reduce ground motion on the retina and thereby enhance the visual salience of a moving bar.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Specifically, flies rely on saccades to track the bar but rapidly engage the smooth optomotor reflex between saccades with a delay as small as 25 ms, consistent with other methods of measurement [7]. During inter-saccadic smooth movement, flies are still capable of perceiving and fixating a visual bar, the corollary of which is that bar tracking is little perturbed by movement of the visual panorama [29]. Robustly tracking the ground in closed-loop would reduce ground motion on the retina and thereby enhance the visual salience of a moving bar.…”
Section: Discussionmentioning
confidence: 77%
“…Similarly, optomotor saccades were triggered by a threshold in the temporal integral of retinal slip. If the visual surroundings were moving simultaneously, saccadic bar fixation was unaffected [29], but flies immediately engaged smooth compensatory movement between every saccade. We propose a novel hybrid control model based upon spatio-temporal integration of visual signals.…”
Section: Introductionmentioning
confidence: 99%
“…Fitting with a sum of exponentials model identifies the time constants and asymptotic amplitudes of STAFs (Fox et al, 2014) and statistical comparison of the fit coefficients would be more sensitive to small differences that may not reach significance under the pure probabilistic approach given here, and should be employed in cases where the mode of differentiation between test and control groups can be hypothesized a priori .…”
Section: Resultsmentioning
confidence: 99%
“…More recently, we have reported several studies of visual figure tracking in fruit flies (Aptekar et al, 2012; Fox and Frye, 2014; Fox et al, 2014) in which we elaborated on this basic technique to develop a representation known as the spatiotemporal action field (STAF). A STAF is defined as a function of time and space that represents a temporal impulse response for some behavioral reaction, evaluated as a function of the position of a feature in the visual field.…”
Section: Introductionmentioning
confidence: 99%
“…Initial work suggested that object position is based primarily on motion detection (Bulthoff & Bulthoff, 1987) but more recent evidence with flies which are not able to detect motion but are able to track objects suggest a separation of these pathways . Orientation behaviour and the optomotor response have been found to work in independent, parallel processing streams in the fly visual system (Aptekar et al, 2012, Fox et al, 2014 but it is unclear where in the fly eye the information captured by photoreceptors gets separated into these different processing streams.…”
Section: Computation Of Object-orientation Behaviourmentioning
confidence: 99%